U-shaped association between waist-to-height ratio and microalbuminuria: A cross-sectional analysis conducted within the Chinese demographic - Xia Huang; Haofei Hu; Lishu He; Zhichao Zhang; Xue Zhang; Hao Yuan; Xiaofang He; Lirong Tu; Feiyuan Liu; Xiuqin Li; Heping Zhang; Yongcheng He (PLoS ONE, 2026)
Background While previous studies have largely overlooked the potential correlation between the waist-to-height ratio (WHtR) and microalbuminuria in Chinese adults, this study aims to rigorously investigate this relationship. Specifically, we examined the potential nonlinear association between WHtR and the presence of microalbuminuria. Methods We conducted a cross-sectional analysis of 33,685 participants from eight regions across China. Microalbuminuria was defined as a urinary albumin-to-creatinine ratio (ACR) > 30 mg/g. The relationship between WHtR and microalbuminuria was assessed using univariate and multivariate logistic regression models. We further explored potential nonlinear associations using Generalized Additive Models (GAM) and evaluated threshold effects to identify critical inflection points. Subgroup analyses were performed to validate the robustness of our findings. Results The cohort (N = 33,685) had a mean age of 57.6 ± 9.27 years and was predominantly females (22,516; 66.8%). The mean WHtR was 0.537 ± 0.06. The median ACR value observed was 9.93 mg/g with an interquartile range (IQR) of 8.23–11.68 mg/g. Notably, the prevalence rate of microalbuminuria detected in the study was 14.4%. In multivariate-adjusted models, each one-unit increase in WHtR was associated with a 48.3% higher likelihood of microalbuminuria development (odds ratio [OR] = 1.483; 95% confidence interval [CI]: 1.410–1.559; p < 0.0001). GAM analyses revealed a significant non-linear association between WHtR and microalbuminuria ( p < 0.0001). Segmented logistic regression identified a WHtR threshold value of 0.497. Above this threshold, the risk of microalbuminuria increased markedly (OR = 11.9, 95% CI 5.14–27.56, p < 0.0001), whereas below this threshold, WHtR was inversely associated with microalbuminuria (OR = 0.107, 95% CI: 0.015–0.748, p = 0.0243). Subgroup analyses further indicated a stronger association among individuals without hypertension and those with a body mass index (BMI) ≥ 24 kg/m 2 , while the association was attenuated in hypertensive participants and those with a BMI < 24 kg/m 2 . Conclusions The risk of microalbuminuria exhibited a U-shaped pattern across WHtR values, with elevated risk at both low and high ends of the spectrum. Moderate central adiposity appeared to confer a protective effect against renal dysfunction. These findings highlighted the dual risks posed by underweight and excessive abdominal obesity and underscored the importance of targeted strategies to prevent obesity-related kidney damage. Future research is warranted to elucidate the mechanisms by which excess visceral fat contributes to renal impairment and to guide interventions aimed at preserving kidney health in diverse populations.